Deep geothermal resources in Quebec and in Colombia: An area that may develop based on French experience on geothermal power plants [Les ressources géothermiques profondes au Québec et en Colombie : un secteur don't le développement pourrait s'inspirer des centrales géothermiques en France] (2016)
Because of an increasing demand in electricity and a necessity of reducing greenhouse gas emissions, several countries envisage the development of the renewable energies. The geothermal energy is a particularly interesting alternative because it allows a production of electricity which is not influenced by weather conditions and it requires relatively restricted surface areas compared, for example, to the area required by a hydroelectric power plant. The literature review presented here summarizes the main characteristics of the geothermal potential in Quebec, in sedimentary basins, and in Colombia, in the area of the Nevado del Ruiz volcanic complex. Currently, in these two regions, the hydro-electric power dominates the electricity production, but there is a similar interest to the development of geothermal power plants. The French sites of Soultz-sous-Forêts in Alsace and Boiling in Guadeloupe are respectively presented as an example of exploitation of geothermal improved systems (Enhanced Geothermal System; EGS) and geothermal resources in volcanic regions. The first site constitutes a model for the future development of the deep geothermal exploitation in Quebec, whereas the second is an example for Colombia. A description of environmental impacts related to the exploitation of deep geothermal resources is presented at the end of this paper.